Pengaruh Motivasi Kerja dan Keterikatan Kerja terhadap Kinerja Karyawan Outsourcing PT Al Quratu Rizky Pratama - Rifqi, Muhammad Naufal; Hadjri, Muhammad Ichsan; Zunaidah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of work motivation and work engagement on the performance of PT Al Quratu Rizky Pratama's outsourced employees. The research method used is a quantitative method. The data used in this research are primary data and secondary data. The sampling technique used the total sampling technique. The samples studied in this study were 80 respondents who were outsourced employees of PT Al Quratu Rizky Pratama. Based on the statistical t test conducted, it can be concluded that the motivation variable partially has a significant effect on employee performance as indicated by a significance value of 0.000 <alpha 0.05. Based on the statistical t test conducted, it can be concluded that the work engagement variable has a positive and significant effect on employee performance as indicated by a significance value of 0.002 <alpha 0.005. Based on the simultaneous f test obtained a significance value of 0.000 <alpha 0.005, it can be concluded that motivation and work engagement as a whole have a significant effect on employee performance. The magnitude of the influence of the independent variable on the dependent variable is 83.7%, the remaining 16.3% is influenced by other variables not included in the research model. Keywords: Motivation, Engagement, Performance